Mandatory changes of specific names to agree in gender with Talitriator Methuen, 1913, which is masculine (Crustacea: Amphipoda: Talitridae) - Nakano, Takafumi (Zootaxa, 2018)
The genus Talitriator Methuen, 1913 was originally erected for T. eastwoodae Methuen, 1913, a talitrid amphipod or “land-hopper” from South Africa that was fixed as the type species of this genus by monotypy. Talitriator now includes seven species of land-hopper inhabiting South Africa as well as Saint Helena and Ascension islands in the Southern Atlantic (Stock & Biernbaum 1994; Griffiths 1999; Horton et al. 2018). Although Methuen (1913) did not explicitly explain the etymology of the generic name, it obviously combines the name of the talitrid type genus Talitrus Bosc, 1802 (stem: Talitr-; from Latin talitrum, a rapping or flick of a finger: Jaeger 1962), with the connecting vowel “i” and the Latin masculine agentive suffix “-ator”. On account of the final suffix, the gender of the name Talitriator is masculine. Under Articles 31.2 and 34.2 of the International Code of Zoological Nomenclature [hereafter “the Code”] (International Commission on Zoological Nomenclature 1999), a Latin adjective that is used as a species-group name must agree in gender with the generic name it is combined with. Article 34.2 further specifies that an incorrect gender ending must be changed (a “mandatory change”, as opposed to either an “emendation” or an “incorrect subsequent spelling”: cf. Article 33.1 of the Code). This gender-agreement rule has largely been ignored in publications concerning species of Talitriator, with adjectival names most often being spelled with the feminine suffix “-a” regardless of generic assignment.